Effect of the flexibility training performed immediately before resistance training on muscle hypertrophy, maximum strength and flexibility - Moriggi Junior, R.; Berton, R.; de Souza, T. M. F.; Chacon-Mikahil, M. P. T.; Cavaglieri, C. R. (European Journal of Applied Physiology, 2017)
Purpose: It has been suggested that flexibility training may reduce the total volume of training during resistance trainings. The purpose of this study was to compare the effect of flexibility training immediately before resistance training (FLEX-RT) versus resistance training without flexibility training (RT) on maximum strength and the vastus lateralis muscle cross-sectional area (CSA). Methods: Participants had each leg assigned to RT or FLEX-RT. Both groups performed four sets of leg extensions to voluntary failure of 80% of one repetition maximum (1RM); however, FLEX-RT performed two sets of 25 s of static stretching before resistance training. Number of repetitions and total volume were calculated during weeks 1-5 and 6-10. Vastus lateralis muscle CSA, 1RM, and flexibility were assessed at baseline and after 10 weeks. Results: The number of repetitions and total training volume were greater for RT than FLEX-RT for weeks 1-5 and 6-10. Regarding the vastus lateralis muscle CSA, a main time effect was observed, however, greater change was observed for RT than FLEX-RT (12.7 and 7.4%, respectively). A main time effect for 1RM was also observed with similar changes for RT and FLEX-RT (12.7 and 12.9%, respectively). Flexibility was increased pre- to post-training for FLEX-RT with greater change for FLEX-RT (10.1%) than RT (2.1%). Conclusion: These results show that performing flexibility training immediately before resistance training can contribute to a lower number of repetitions, total volume, and muscle hypertrophy.